Molecular Chaperone BRICHOS Inhibits CADASIL-Mutated NOTCH3 Aggregation In Vitro - Oliveira, Daniel V.; Svensson, Julia; Zhong, Xueying; Biverstål, Henrik; Chen, Gefei; Karlström, Helena (Frontiers in Molecular Biosciences, 2022)
CADASIL (cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy) is the most common familial form of stroke, which is caused by mutations located in the epidermal growth factor (EGF)-like repeats of the NOTCH3 gene. Mutations cause the NOTCH3 (N3) protein to misfold and aggregate. These aggregates will be a component of granular osmiophilic material, which when accumulated around the arteries and arterioles is believed to cause the degradation of vascular smooth muscle cells (VSMC). VSMC degradation affects blood flow regulation and leads to white matter and neuronal death. Currently, there is no treatment for CADASIL. The dementia-relevant BRICHOS domain is a small multitalented protein with functions that include ATP-independent chaperone-like properties. BRICHOS has been shown to prevent the aggregation of both fibrillar and non-fibrillar structures. Therefore, the objective of this study is to investigate whether BRICHOS exhibits anti-aggregating properties on a recombinant CADASIL-mutated N3 protein consisting of the first five repeats of EGF (EGF1-5), harbouring a Cysteine instead of an Arginine in the position 133 (R133C). We found that the N3 EGF1–5 R133C mutant is more prone to aggregate, while the wildtype is more stable. Recombinant human Bri2 BRICHOS is able to interact and stabilize the R133C-mutated N3 protein in a dose-dependent manner. These results suggest an anti-aggregating impact of BRICHOS on the N3 EGF1-5 R133C protein, which could be a potential treatment for CADASIL.